Productive efficiency of specialty and conventional coffee farmers in Costa Rica: Accounting for technological heterogeneity and self-selection - Meike Wollni; Bernhard Brümmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2009)
A steep decline in coffee prices at the producer level led to considerable pressure for farmers in Costa Rica and producer countries all over the world. One possible reaction was moving to specialty markets, where price pressure was perceived to be lower. We use original survey data from 2002/03 and 2003/04 to analyze the factors influencing efficiency levels of conventional and specialty coffee farmers. Controlling for selectivity bias, we find that technical efficiency in the two subsamples is influenced by both identical and divergent factors. Among the former, additional income activities increase efficiency. Among the divergent factors, experience, bookkeeping, and the number of adult household members are found to have a significant impact in the specialty coffee model. In the case of conventional coffee farmers, membership in cooperatives leads to higher farm-level efficiency. Based on the results, we derive policy recommendations to improve farmers' production performance and ability to cope with the effects of the coffee crisis. These policy measures include the provision of extension services with respect to accounting methods, the creation of income opportunities in rural areas, and the support of farmer-owned cooperatives.
Keywords: Q12; D24; 330; Coffee; Costa Rica; Stochastic frontier analysis; Sample Selectivity; Specialty markets; Technological heterogeneity